Development of Web-Based Learning Media Using Problem-Based Learning (PBL) Approach on Scratch Material to Enhance Learning Motivation of Seventh-Grade Junior High School Students - Ahmad, Fathul Luthfillah; Nugroho, Azis Luki; Anjarsari, Delvi Dwi; Rahmayanti, Ririn; Ningrum, Gres Dyah Kusuma; Arifin, M. Zainal; Satriyatma, Avo; Cakir, Gulsun Kurubacak (Universitas Negeri Malang, 2024)
The low motivation of students to understand programming material at the junior high school level presents a challenge in informatics education. This study aims to develop web-based learning media using a Problem-Based Learning (PBL) approach on Scratch material to increase the learning motivation of seventh-grade junior high school students. The Research and Development (R&D) methodology used the ADDIE model, encompassing five stages: analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, and questionnaires using a mixed-methods approach to obtain in-depth and measurable results. The analysis showed that the learning media was highly valid, with a 95.83 percent rating from content experts and 93.84 percent from media experts, and received an excellent response from student trials. Motivation assessments revealed a significant increase in student learning motivation from 72.18 percent (high) before using the media to 87.85 percent (very high) after its implementation. This learning media was positively received by students, deemed engaging, and made it easier for them to grasp fundamental programming concepts. Therefore, the web-based learning media using the PBL approach has proven effective in supporting increased student learning motivation and contributes to the advancement of informatics education in junior high schools.